The Prognoses of Young Women With Breast Cancer (≤35 years) With Different Surgical Options: A Propensity Score Matching Retrospective Cohort Study - Li, Pei; Li, Lun; Xiu, Bingqiu; Zhang, Liyi; Yang, Benlong; Chi, Yayun; Xue, Jingyan; Wu, Jiong (Frontiers in Oncology, 2022)
BACKGROUND: Surgery is the most important local treatment for young women with breast cancer(YWBC), and there is still a lack of prospective studies comparing surgical options for recurrence and survival. We retrospectively compared the effects of surgical options on disease-free survival (DFS) and overall survival (OS) of YWBCs at Fudan University Shanghai Cancer Center (FUSCC). METHODS: YWBC (age ≤ 35 years) who underwent surgery for FUSCC between 2008 and 2016 were retrospectively analyzed and divided into three groups according to surgical options: (1) breast-conserving surgery (BCS), (2) mastectomy alone (M), and (3) mastectomy with reconstruction (RECON). The DFS and OS survival outcome rates from the three surgical options were compared using the Kaplan–Meier method and Cox regression model. Propensity score matching (PSM) was also used to balance the baseline characteristics to eliminate selection bias. RESULTS: A total of 1520 YWBCs were enrolled with a median follow-up of 5.1 years, including 524 patients (34.5%) who underwent BCS, 676 patients (44.5%) who underwent M, 320 patients (21.1%) who underwent RECON. The 5-year DFS rates were 96%, 87%, and 93%, respectively (P < 0.001); the 5-year OS rates were 98%, 94%, and 97%, respectively(P = 0.002). Multivariate Cox analysis showed that DFS and OS were significantly improved in patients undergoing BCS compared with those undergoing M, with HRs of 0.448 [95% CI 0.276–0.728; P = 0.001] and 0.405 [95% CI 0.206–0.797, P = 0.009], respectively. After PSM, DFS and OS rates were significantly improved in patients undergoing BCS compared to patients undergoing M (DFS, P = 0.001; OS, P = 0.009); RECON was also improved compared to patients undergoing M in terms of DFS and OS, but the difference was not statistically significant (DFS, P = 0.164; OS, P = 0.130). CONCLUSIONS: The surgical options were independent factors affecting DFS and OS in YWBC, and the DFS and OS rates were significantly improved in the BCS group compared to those in the M group. BCS is preferred for early YWBC, and RECON is the best option for remodeling the body images of YWBC who do not have breast-conserving conditions.